The comparsion of teo different asophageal motility cathaters recording lower esophageal sphincter pressure - Serhat BOR,; Oktay TEKEŞİN,; Hakan YÜCEYAR,; Nadir YÖNETÇİ,; Hanefi ÇAVUŞOĞLU, (Turkish Journal of Gastroenterology, 2019)
-